Effects of Rovalpituzumab Tesirine on Ventricular Repolarization in Patients With Small‐Cell Lung Cancer - Jonathan W. Goldman; Minal Barve; Jyoti D. Patel; Antoinette Wozniak; Afshin Dowlati; Alexander Starodub; Taofeek K. Owonikoko; William Edenfield; Scott A. Laurie; Daniel Da Costa; Satwant Lally; Martina Koch; et al. (Wiley, 2021)
Small cell lung cancer (SCLC) is a leading cause of cancer death worldwide, with few treatment options. Rovalpituzumab tesirine (Rova‐T) is an antibody‐drug conjugate that targets delta‐like 3 on SCLC cells to deliver a cytotoxic payload directly to tumor cells. In this study, the cardiac safety profile of Rova‐T was assessed by evaluating changes in QT interval, electrocardiogram (ECG) waveform, heart rate, and proarrhythmic adverse events (AEs) after treatment with Rova‐T in patients with previously treated extensive‐stage SCLC. Patients underwent ECG monitoring for 2 weeks after each of 2 i.v. infusions of 0.3 mg/kg Rova‐T over 30 minutes, administered 6 weeks apart. Forty‐six patients received at least one dose of Rova‐T. At the geometric mean Rova‐T maximum serum concentration of 7,940 ng/mL, ECG monitoring showed no significant changes in the Fridericia‐corrected QT (QTcF) interval; the upper limit of the 2‐sided 90% confidence interval did not exceed 10 msec for any time point. There were no clinically significant changes in QRS or PR intervals, ECG waveforms, or heart rate after Rova‐T administration. All patients experienced a treatment‐emergent AE (TEAE); 78% had a grade ≥ 3 TEAE, 59% had a serious TEAE, and 41% had a cardiac‐related TEAE. The TEAEs that might signal proarrhythmia tendencies were uncommon. Confirmed partial responses were observed in 24% of patients. Based on the evaluation of ECG data collected in this study from patients treated with Rova‐T at 0.3 mg/kg i.v. administered every 6 weeks, a QTcF effect of clinical concern can be excluded.